SECRETS OF LONG LIFE - Qo’ldosheva Mo’tabar Muhtarovna, (TADQIQOTLAR, 2026)
Everyone dreams of living a long, healthy, and happy life. Throughout history, people have searched for the secret of longevity. Today, scientists and health experts agree that there is no single secret or magic solution for living a long life. Instead, longevity is the result of many healthy habits practiced consistently over time. A long life is not only about reaching an old age but also about maintaining physical, mental, and emotional well-being throughout life.   Many people who live beyond the age of 90 or even 100 share common lifestyle characteristics. They eat nutritious food, stay physically active, maintain positive social relationships, manage stress effectively, and avoid harmful habits. Modern research has shown that genetics play a role in determining lifespan, but lifestyle choices have an even greater influence. By adopting healthy behaviors, people can increase their chances of living a longer and healthier life.   This article discusses the most important secrets of long life and explains how they contribute to overall health and longevity.